Dampak Indikator Makro Ekonomi terhadap Dana Pihak Ketiga Perbankan Syariah - Saekhu, Saekhu (Economica: Jurnal Ekonomi Islam, 2017)
This study was undertaken to analyze the effects of macroeconomic indicators (SBI interest rate, exchange rate, inflation, Indonesia Composite Index and GDP) to deposits liabilities of Islamic Banking in Indonesia. Analysis unit of this study is the Islamic Banking in Indonesia during the period 1998-2008. For the empirical analysis in this study it is used the data on aggregate time series of the monthly period from January 2003 to December 2010. Source data taken from publication of Bank Indonesia, in the form of Annual Report Bank Indonesia,Â  Indonesia Bank Monetary Statement Of Policy, Statistics Economic and Financial Indonesia, Islamic Banking Statistics (Statistik Perbankan Syariah/SPS) and publication report from Badan Pusat Statistik (BPS). This study uses Linear Regression analysis with Ordinary Least Square (OLS) method. The result show that macroeconomic indicators have impact on Funding (deposit liabilities) of Bank Syariah Mandiri, the SBI interest rate have negative impact, while exchange rate, inflation, Indonesia Composite Index and GDP have positive impact. Based on the same method, it shows that GDP has positive on Funding of Islamic Banking in Indonesia.Penelitian ini dilakukan untuk menganalisis dampak indikator makro ekonomi (suku bunga SBI, nilai tukar, inflasi, Indeks Harga Saham Gabungan Indonesia dan PDB) terhadap deposito (Dana Pihak Ketiga) Perbankan Syariah di Indonesia. Unit analisis penelitian ini adalah Perbankan Syariah di Indonesia selama periode 1998-2008. Analisis empiris dalam penelitian ini menggunakan data kumpulan waktu agregat periode bulanan dari Januari 2003 sampai Desember 2010. Sumber data diambil dari publikasi Bank Indonesia, berupa Laporan Tahunan Bank Indonesia, Laporan Kebijakan Moneter, Statistik Ekonomi dan Keuangan Indonesia/SEKI), Statistik Perbankan Syariah (SPS) dan laporan publikasi Badan Pusat Statistik (BPS). Penelitian ini menggunakan analisis Regresi Linier dengan metode Ordinary Least Square (OLS). Hasil menunjukkan bahwa indikator makro ekonomi berdampak pada pendanaan (deposito) Bank Syariah Mandiri, suku bunga SBI memiliki dampak negatif, sedangkan nilai tukar, inflasi, Indeks Harga Saham Gabungan Indonesia dan PDB berdampak positif. Berdasarkan metode yang sama, PDB positif terhadap Pendanaan Perbankan Syariah di Indonesia.